How media empower the vulnerable: Using community structure theory to analyze relationships between demographics and health reporting - John C. Pollock (Elsevier, 2020)
Instead of studying the impact of media on society, the traditional "top down" orientation of most communication studies scholars, this keynote presentation adopted the opposite perspective, exploring the "bottom-up" impact of "society" on "media". Unlike conventional "agenda-setting theory", which suggests that nationally prominent news media set issue "agendas" for other news media and public opinion, and also unlike the "guard dog" view that media essentially protect the interests of political and economic elites, the "community structure theory" explores links between different community (typically city or nation-state) demographics and variations in reporting on critical health concerns. Summarizing his scholarship on health communication presented and published over decades, the speaker outlined community structure theory's illumination of two overall patterns in US and cross-national coverage of health communication issues. In US coverage, broad measures of economically "buffered" privilege (educational, income, or occupational advantage) are linked to "favorable" or "government responsibility" coverage of health issues, and specific measures of "health" privilege (physicians, hospitals) are connected to "favorable" or "government responsibility" coverage promoting selected health issues. In cross-national coverage, specific measures of national "health vulnerability" (such as percent without improved water access, infant mortality rate) are linked to "government" responsibility coverage for selected health issues (human trafficking, water handling/contamination). In addition, broad measures of "macro" vulnerability conditions (agricultural dependence, political instability) are associated with "government" responsibility coverage for a wide range of health issues (genetically modified foods, drug trafficking, condom promotion, and food security). Overall, community structure theory's "bottom up" perspective reveals how the vulnerable are empowered by their demographic alignment with variations in health communication.